In vaccinated individuals serum bactericidal activity against B meningococci is abrogated by C5 inhibition but not by inhibition of the alternative complement pathway - Ispasanie, Emma; Muri, Lukas; Schmid, Marc; Schubart, Anna; Thorburn, Christine; Zamurovic, Natasa; Holbro, Thomas; Kammüller, Michael; Pluschke, Gerd (Frontiers in Immunology, 2023)
Dysregulation of complement activation causes a number of diseases, which can be treated with inhibitors of the complement components C5 and/or C3. However, complement is required for serum bactericidal activity (SBA) against encapsulated Gram-negative bacteria. Therefore, C3 and C5 inhibition increases the risk of invasive disease, in particular by Neisseria meningitidis. As inhibitors against complement components other than C3 and C5 may carry a reduced risk of infection, we compared the effect of inhibitors targeting the central complement component C3, the alternative pathway (fB and fD), the lectin pathway (MASP-2) and the terminal pathway (C5) on SBA against serogroup B meningococci. Serum from adults was collected before and after vaccination with the meningococcal serogroup B vaccine 4CMenB and tested for meningococcal killing. Since the B capsular polysaccharide is structurally similar to certain human polysaccharides, 4CMenB was designed to elicit antibodies against meningococcal outer membrane proteins. While only a few pre-vaccination sera showed SBA against the B meningococcal isolates tested, 4CMenB vaccination induced potent complement activating IgG titers against isolates expressing a matching allele of the bacterial cell surface-exposed lipoprotein Factor H binding protein (fHbp). SBA triggered by these cell surface protein-specific antibodies was blocked by C5 and reduced by C3 inhibition, whereas alternative (factor B and D) and lectin (MASP-2) pathway inhibitors had no effect on SBA of post-4CMenB vaccination sera. Compared to SBA triggered by A,C,W,Y capsule polysaccharide conjugate vaccination, SBA against B meningococci expressing a matching fHbp allele was thus remarkably resilient against alternative pathway inhibition.